A review on the applications of carbon nanotubes / Siti Sumaiyah Sheikh Abdul Aziz …[et al.] - Sheikh Abdul Aziz, Siti Sumaiyah; Harun, Nurhana Ilmira; Salleh, Nunshaimah; Senawi, Syamsir Akmal; Hashim, Azhan (2014)
This study describes a review of the applications of carbon nanotubes in various field. This paper consists of two main sections categorized by CNTs synthesis and properties of carbon nanotubes in field electron emission. Finally the review is concluded with several applications on carbon nanotubes focusing more in their properties. Based on study, CNT had remarkable electronic and mechanical properties that lead to unbelievable forms of power, and conductivity. The exceptional properties and characteristics of CNTs provide the potential in various applications such as electrochemical devices, nanoelectronics, composite materials, and sensors.